The claustrum’s proposed role in consciousness is supported by the effect and target localization of Salvia divinorum - Stiefel, Klaus M.; Merrifield, Alistair; Holcombe, Alex O. (Frontiers in Integrative Neuroscience, 2014)
This article brings together three findings and ideas relevant for the understanding of human consciousness: (I) Crick's and Koch's theory that the claustrum is a “conductor of consciousness” center crucial for subjective conscious experience. (II) Subjective reports of the consciousness-altering effects the plant Salvia divinorum, whose primary active ingredient is salvinorin A, a -opioid receptor agonist. (III) The high density of -opioid receptors in the claustrum. Fact III suggests that the consciousness-altering effects of salvinorin A are due to a κ-opioid receptor mediated inhibition of primarily the claustrum and, additionally, the deep layers of the cortex, mainly in prefrontal areas. Consistent with Crick & Koch’s theory that the claustrum plays a key role in consciousness, our analysis of the subjective effects of Salvia divinorum finds that salvia disrupts certain facets of consciousness much more than the largely-serotonergic hallucinogen LSD. Based on this data and on the relevant literature, we suggest that the claustrum does indeed serve as a conductor for certain aspects of higher-order integration of brain activity, while integration of auditory and visual signals mostly relies on coordination by other areas including parietal cortex and the pulvinar.